Sunspots are Correlated with Foliar pH in Grapevines - Giorgio, Masoero; Alberto, Cugnetto; Giuseppe, Sarasso; Giusto, Giovannetti; Marco, Nuti (Journal of Agronomy Research, 2019)
Foliar pH is a specific multifaceted parameter that is sensitive to a deficit in soil water and to temperature variations. It also represents a tool that can be used to rapidly phenotype the symbiosis induced in several crops by bio-fertilizers containing Arbuscular Mycorrhizal Fungi. Yearly decreases in foliar pH, which dropped from 3.73 in 2015 to 3.15 in 2017 and then stabilized at around 3.13, have been observed in an experimental vineyard near Torino (Italy) in six grapevine cultivars. In this paper, these curious, original results have been paired with the average sunspots of the 24th sun cycle, proximal to its endpoint. The paired values were highly correlated (r 0.95 P< 0.01), with close parabolic patterns. A lowering in foliar pH has been correlated with a modification of the leaf composition, as characterized by the higher hydration and reinforced wall. An increase in the circulating acidity of the plants has been hypothesized to interfere in a diminution in the general predisposition to block parasite attacks. From this perspective, the retrieval of several historic outbreaks and the long-term systematic monitoring of mud and Erwinia amylovora frequencies have suggested that the hypothesis that links the solar minima with dysfunctions of the plant-pest relationships cannot always be rejected. Cosmic influences pertaining to UV variations are poorly understood in plant physiopathology. Foliar pH appears to be a rapid and simple tool to unveil high-level mechanisms. It is this simple parameter that physiologists and geneticists, but also agronomists, are asked to consider.
Keywords: Foliar pH; grapevine; sunspots; wall composition; leaf hydration; NIRS; stress outbreak correlation; phenotyping; climate change.